A Low-Powered and Highly Selective Trap for Male Aedes (Diptera: Culicidae) Surveillance: The Male Aedes Sound Trap. Issue 1 (2nd August 2020) - Staunton, Kyran M; Crawford, Jacob E; Liu, Jianyi; Townsend, Michael; Han, Yu; Desnoyer, Mark; Howell, Paul; Xiang, Wei; Burkot, Thomas R; Snoad, Nigel; Ritchie, Scott A
Abstract: As Aedes aegypti (Linnaeus, Diptera: Culicidae) expands its global distribution and vectors a range of debilitating arboviruses there is an increased need for enhanced mosquito surveillance. Consequently, we developed a Male Aedes Sound Trap (MAST) that requires minimal power and is highly species-specific. Two different versions of the MAST were developed, one that uses synthetic pyrethroid to kill captured mosquitoes (MAST Spray) and another which has an internal divider to create a killing chamber in which a sticky panel can be placed to capture mosquitoes (MAST Sticky). We compared weekly capture rates of male Ae. aegypti and bycatch from the two MAST versions to those from BG-Sentinel (BGS) traps and Sound-producing BG-Gravid Aedes Traps (SGATs) throughout Cairns, northern Australia. Weekly mean male Ae. aegypti catches did not significantly differ between trap types. However, the rate of positive weekly detections of male Ae. aegypti was lower for the MAST Sticky than the other three trap types. The MASTs sampled significantly fewer mosquitoes other than male Ae. aegypti, than either the BGS trap or the SGAT. Also, the MASTs and SGATs all caught significantly less non-Culicidae bycatch than the BGS traps. Consequently, we have developed a versatile male Ae. aegypti trap which is potentially of great benefit to Ae. aegypti surveillance programs.